Mesenchymal Stem Cell-Derived Exosomes: A Novel Approach to Diabetes-Associated Cognitive Impairment - Ran Q; Tian H; Lin J; Wang H; Wang B; Chen Z; Song D; Gong C (Dove Medical Press, 2023)
Qingsen Ran,1 He Tian,1 Jian Lin,1 Han Wang,2 Bo Wang,1 Zhixin Chen,1 Da Song,1 Chunzhu Gong1 1Department of Science and Education, Shenzhen Pingle Orthopedic Hospital (Shenzhen Pingshan Traditional Chinese Medicine Hospital), Shenzhen, Guangzhou Province, 518118, People's Republic of China; 2Department of Gastroenterology, Affiliated Hospital of Changchun University of Chinese Medicine, Changchun, Jilin Province, 130021, People's Republic of ChinaCorrespondence: Chunzhu Gong, Email gczq_82@126.comAbstract: The progression of diabetes frequently results in a myriad of neurological disorders, including ischemic stroke, depression, blood-brain barrier impairment, and cognitive dysfunction. Notably, diabetes-associated cognitive impairment, a prevalent comorbidity during the course of diabetes, progressively affects patients' cognitive abilities and may reciprocally influence diabetes management, thereby severely impacting patients' quality of life. Extracellular vesicles, particularly nanoscale exosomes, have garnered considerable attention in recent years. These exosomes carry and transfer various functional molecules, such as proteins, lipids, and diverse non-coding RNAs, serving as novel regulators and communicators in intercellular interactions. Of particular interest, mesenchymal stem cell-derived exosomes (MSC-Exos) have been reported to traverse the blood-brain barrier and ameliorate intracerebral pathologies. This review elucidates the role of MSC-Exos in diabetes-related cognitive impairment, with a focus on their applications as biomarkers, modulation of neuronal regeneration and synaptic plasticity, anti-inflammatory properties, antioxidative effects, and their involvement in regulating the functionality of β-amyloid proteins during the course of cognitive impairment. The immense therapeutic potential of MSC-Exos in the treatment of diabetes-induced cognitive dysfunction is emphasized.Keywords: diabetes-associated cognitive impairment, mesenchymal stem cell-derived exosomes, blood-brain barrier, neuronal regeneration, synaptic plasticity